A Risk-Stratified Management Framework for Tattooed Patients in MRI: Integrating Physicochemical Properties with Clinical Safety Protocols - Vasiliki Kefala; Eleni Andreou; Vasiliki-Sofia Grech; Niki Tertipi; Eleni Sfyri; Efstathios Rallis (Applied Sciences, 2026)
Tattooing has transitioned from a specialized segment practice to a mainstream form of self-expression, with global prevalence estimates ranging from 20% to 30% in adult populations across Western countries. As the tattooed demographic expands, the intersection between tattoo pigments and magnetic resonance imaging (MRI) has emerged as a clinically relevant concern. This review provides a comprehensive analysis of the physicochemical properties of modern tattoo inks, their interactions with MRI-generated electromagnetic fields, and the resultant safety considerations and imaging artifacts. We examine the mechanisms underlying MRI-related adverse events—including thermal effects, magnetically induced forces, and radiofrequency-induced currents—and contextualize their clinical significance based on current evidence. Furthermore, we explore how tattoo pigments compromise image quality through susceptibility artifacts, signal voids, and geometric distortions, with particular attention to anatomical regions frequently tattooed in contemporary practice. The regulatory landscape governing tattoo ink composition is critically assessed, highlighting discrepancies between jurisdictions and the implications for patient safety. Finally, we propose evidence-based clinical recommendations for managing tattooed patients undergoing MRI examinations and identify key knowledge gaps warranting further investigation.